PERUBAHAN KEBIJAKAN PERDAGANGAN INTERNASIONAL PASCA-BREXIT, DENGAN STUDI KASUS BRITANIA DAN UNI EROPA. - Pratama, Aldi Adi; Saputra, Muhammad Renaldi; Nainggolan, Zacky Naoval (Jurnal Studi Ilmu Politik, 2024)
In the United Kingdom, since 2016, discourse on the Brexit policy has emerged. This policy includes the United Kingdom's exit from the European Union (EU). This plan is due to financial contributions, namely that the UK is one of the largest contributors to the European Union budget. The official exit of the UK from the European Union on January 31 2020 at 11 pm GMT resulted in changes in economic flows in Europe. The aim of this research is to examine in more depth the research on changes in the dynamics of post-Brexit international trade, with case studies of the UK and the European Union. The method in this research uses a literature study and literature review approach. Literature study analysis has the advantage of providing a comprehensive review, such as a broad overview but focusing more on aspects of the problem raised from different points of view. The literature study approach is also able to identify research gaps according to trends and developments. The research results reveal that the UKGovernment's strategy includes implementing seasonal worker visa laws, implementing a points-based immigration system,formulating the 2020 agricultural policy, encouraging local workers and automation. Investment concerns which are part of the trade-economic aspect, from the Brexit policy itself, caused the British economy to experience a decline, making other countries such as Japan worried that their investments in the UK would suffer losses. But on the other hand, there is a positive impact for the UK with the existence of the Single Market.